The Potential of Physical Exercise to Mitigate Radiation Damage—A Systematic Review - Kim, David S.; Weber, Tobias; Straube, Ulrich; Hellweg, Christine E.; Nasser, Mona; Green, David A.; Fogtman, Anna (Frontiers in Medicine, 2021)
There is a need to investigate new countermeasures against the detrimental effects of ionizing radiation as deep space exploration missions are on the horizon. Objective: In this systematic review, the effects of physical exercise upon ionizing radiation-induced damage were evaluated. Methods: Systematic searches were performed in Medline, Embase, Cochrane library and the databases from space agencies. Of 2798 publications that were screened, 22 studies contained relevant data that were further extracted and analyzed. Risk of bias of included studies was assessed. Due to the high level of heterogeneity, meta-analysis was not performed. Five outcome groups were assessed by calculating hedges g effect sizes and visualized using effect size plots. Results: Training decreased radiation-induced DNA damage, oxidative stress, and inflammation, while increasing antioxidant activity. Although the results were highly heterogeneous, there was evidence for a beneficial effect of exercise in cellular, clinical, and functional outcomes. Conclusions: Out of 72 outcomes, 68 showed a beneficial effect of physical training when exposed to ionizing radiation. As the first study to investigate a potential protective mechanism of physical exercise against radiation effects in a systematic review, the current findings may help inform medical capabilities of human spaceflight and may also be relevant for terrestrial clinical care such as radiation oncology.